2010
DOI: 10.1063/1.3511441
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic effects on toroidal momentum transport

Abstract: A parametric study of electromagnetic effects on toroidal momentum transport has been performed. The work is based on a new version of the Weiland model where symmetry breaking toroidicity effects derived from the stress tensor have been taken into account. The model includes a self-consistent calculation of the toroidal momentum diffusivity, which contains both diagonal and off-diagonal contributions to the momentum flux. It is found that electromagnetic effects considerably increase the toroidal momentum pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…Full agreement was obtained between the fluid approach in [60] and the gyrofluid equations in [57,58]. We have here included electromagnetic effects for the toroidal momentum [15,65,70]. Also electromagnetic effects may enhance the pinch [70].…”
Section: Momentum Transportmentioning
confidence: 92%
“…Full agreement was obtained between the fluid approach in [60] and the gyrofluid equations in [57,58]. We have here included electromagnetic effects for the toroidal momentum [15,65,70]. Also electromagnetic effects may enhance the pinch [70].…”
Section: Momentum Transportmentioning
confidence: 92%
“…The net toroidal momentum flux is outward in equilibrium since there is a torque deposition in the interior. There is, however, a strong inward component of the toroidal flux which enhances the inward peaking 9 . We notice that the simulated profiles have somewhat more pronounced barriers (in particular Vtor) but the central values are quite similar to the experimental.…”
Section: Simulationsmentioning
confidence: 99%
“…It was recently found that electromagnetic effects increase the toroidal momentum pinch 9 . The first term on the right hand side is the ExB convection in the background velocity gradient.…”
Section: Formulationmentioning
confidence: 99%
“…In previous works, electromagnetic effects on toroidal momentum flux including diffusivity and off-diagonal component were reported [21,22]. The intrinsic stress force driven by electromagnetic turbulence has also been done [23,24].…”
Section: Introductionmentioning
confidence: 99%